Epidemiology, Clinical Characteristics, Risk Factors, and Outcomes of Candidemia in a Large Tertiary Teaching Hospital in Western China: A Retrospective 5-Year Study from 2016 to 2020 - Jie Hou; Jin Deng; Ya Liu; Weili Zhang; Siying Wu; Quanfeng Liao; Ying Ma; Mei Kang (MDPI AG, 2022)
The aim of this study was to investigate the current status of candidemia and evaluate the clinical characteristics, risk factors and outcomes among different species. We conducted a retrospective study by univariate and multivariate analysis between Candida albicans and non-albicans Candida (NAC) species in a Chinese national medical center from 2016 to 2020. Among the 259 episodes, C. albicans (38.6%) was the leading species, followed by C. tropicalis (24.3%), C. parapsilosis (20.5%), and C. glabrata (12.4%). Most C. albicans and C. parapsilosis were susceptible to nine tested antifungal agents, whereas C. tropicalis showed 30.2~65.9% resistance/non-wild-type to four azoles with great cross-resistance, indicating that fluconazole should not be used for empirical antifungal treatment. In multivariable models, the factor related to an increased risk of NAC was glucocorticoid exposure, whereas gastrointestinal hemorrhage and thoracoabdominal drainage catheters were associated with an increased risk in C. albicans. Subgroup analysis revealed leukemia and lymphoma, as well as glucocorticoid exposure, to be factors independently associated with C. tropicalis in comparison with C. albicans candidemia. No significant differences in 7-day mortality or 30-day mortality were observed between C. albicans and NAC. This study may provide useful information with respect to choosing empirical antifungal agents and exploring differences in molecular mechanisms.